Factors Associated With Anemia Incidence Among Pregnant Women At Kapau Public Health Center, Agam Regency - Andi Yusman; Dwi Noerjoedianto; M.Ridwan; Budi Aswin; Ashar Nuzulul Putra (CV. AFDIFAL MAJU BERKAH, 2026)
This study aimed to analyze the factors associated with anemia among pregnant women in the working area of Kapau Public Health Center, Agam Regency, Indonesia, in 2022. The study employed a quantitative analytical design with a cross-sectional approach. A total of 126 third-trimester pregnant women were selected using simple random sampling from the population of pregnant women attending antenatal care services. Data were collected through structured questionnaires assessing knowledge, educational level, family income, and adherence to iron (Fe) tablet consumption, while anemia status was determined based on hemoglobin levels recorded in maternal health books. Data were analyzed using the Chi-square test with a 95% confidence level (α = 0.05). The findings revealed significant associations between maternal knowledge and anemia incidence (p < 0.05), as well as between adherence to Fe tablet consumption and anemia incidence (p < 0.05). In contrast, educational level and family income were not significantly associated with anemia among pregnant women (p > 0.05). These results indicate that behavioral factors, particularly knowledge and compliance with iron supplementation, play a more important role in preventing anemia than sociodemographic factors. In conclusion, improving maternal knowledge and strengthening adherence to iron tablet consumption are essential strategies to reduce anemia among pregnant women. Health promotion and continuous monitoring by healthcare providers are recommended to improve maternal health outcomes.